Inside Out with Knowledge Management toward Internal Communication Facilitating Transformational Change Efficiency - Ousanee Sawagvudcharee; Maurice Yolles (International Journal of Economics Business and Management Research, 2022)
This study is designed to focus on analyzing how to facilitate transformational change toward knowledge management and internal communication, in the form of internal marketing. It employed a case study approach (as a privatization) wherein a qualitative data collection was conducted. It used interviews to identify key issues from the perspective of those employed in the case study organization as well as the documentary methods. With special reference to Thailand, the case of the privatization of the Provincial Electricity Authority (PEA) was examined as a transformational change. The findings of the research will provide a comprehensive insight into the concept of privatization in a state-owned enterprise (SOE) in the context of internal marketing. As such the results cannot be generalized to other organizational environments because they have different complexity systems. On the other hand, the research should provide significant insights into how knowledge management in the direction of internal communication can facilitate a privatization process in a state-owned enterprise in Thailand. It is anticipated that it will present these notions in positive light, thus encouraging more widespread application to assure successful outcomes in similar projects.
Keywords: International Business and FDI